Percolation of heterogeneous flows uncovers the bottlenecks of infrastructure networks - Homayoun Hamedmoghadam (Nature Portfolio, 2021)
Infrastructure networks are characterized by fluctuations of flow demand between different points and temporal congestion or overload on flow pathways. Hamedmoghadam et al. identify congestion bottlenecks in networks relevant to communication, transportation, water supply, and power distribution.